Spirituality and beliefs of Colombian internal conflict survivors - Villegas, Diana L. (HTS teologiese studies, 2019)
Remarkable stories of resilience and forgiveness have been reported in the wake of the internationally recognised peace process in Colombia. From the perspective of Christian spirituality, this study seeks to understand the individual and communal values, beliefs and practices that made the reconciliation and restoration of a community possible after severe dislocation and violence, some of it of neighbour against neighbour. Interviews conducted in the field (in San Carlos, Antioquia, Colombia) and transcribed by the author were used as texts. Transcripts were studied taking into account cultural, geographic and historical contexts. I found that a deeply rooted family- and community-based Catholic culture, brought by the Spanish in the 16th century and continuing to influence this rural area, offered values, beliefs and devotional practices that gave meaning, strength and empowered the ability to forgive. Also, psychological and pastoral tools for grieving, together with sociological and political values about reconciliation and the rebuilding of a community’s fabric, intertwined with the religious values to deepen the capacity for reconciliation and community rebuilding. The experiences of these interviewees reveal a form of Christian spirituality lived through family and community ties that was augmented and empowered by values and practices of non-religious institutions, making possible significant personal and communal journeys of transformation and the concomitant remarkable resilience.